Effect of the groundwater fluctuation process on crop growth in Shijin irrigation district. Issue 9 (13th August 2022) - Fawen, Li; Yutong, Liu; Jun, Fu
Abstract: To achieve the stability of grain production, it is necessary to analyze the impact of groundwater change on crop yield. In this paper, the AquaCrop model was established in the Shijin irrigation district. First, the meteorological data, crop data, management data, soil data and simulation settings were collected as the input data. Second, the calibration and validation of the model were carried out. The RE was all within ±20%, the standard root mean square error (NRMSE) and the coefficient of residual mass (CRM) of cotton were 0.0593 and −0.0173, those of summer maize were 0.0892 and 0.0266 and those of winter wheat were 0.0779 and 0.0273, respectively. The model was accurate and successfully applied. The effect of groundwater change on crop yield in the whole growth period and different growth stages was studied. The results showed that summer maize and winter wheat were less sensitive to groundwater. The minimum groundwater depth for maize and wheat was 1.1 and 1.0 m, respectively. Cotton was more sensitive to groundwater. The suitable groundwater depth of cotton was 1.1–2.0 m. The maximum suitable groundwater depth of cotton in the sowing and seedling stage was 1.5 m. The minimum suitable groundwater depth of cotton in the bud stage and the floweri20ng and boll stage was 1.1 m. HIGHLIGHTS: Compared with previous studies using fixed groundwater depth, this paper studied the effect of the dynamic groundwater fluctuation process on the crop growth process. The response of crop yield to the groundwater depth change process in the whole growth was analyzed. Cotton, which is most sensitive to groundwater, was selected from three crops and its response to groundwater at different growth stages was analyzed. Graphical Abstract